Argus’ Wink: On the Advantages of Reading Ovid’s Metamorphoses with One Hundred Eyes - Bednarek, Bartłomiej (Polskie Towarzystwo Filologiczne, 2023)
The article discusses the episode in Ovid’s Metamorphoses in which Hermes lulls Argus to sleep by telling him the story of Pan and Syrinx and then cuts his head off. The passage has often been read by scholars as a metanarrative joke that Ovid makes about tales that his readers may find too boring to follow. Argus is thus supposed to be a figure of a disengaged reader. As I argue, however, Ovid’s text makes it clear that Argus was simply too naïve and too profoundly captivated by the story to resist its charm. Therefore, he should be taken as a figure of a childish listener, whom Ovid did not intend to exclude from enjoying his poem.